A rare primary liver tumour case report: 53-year-old man with primary hepatic leiomyosarcoma - Triyanta Yuli Pramana; Paulus Kusnanto; Aritantri Darmayani; Didik Prasetyo; Rahmat Nugroho; Brian Wasita; Widiastuti (Faculty of Medicine, Universitas Islam Indonesia, 2022)
Primary hepatic leiomyosarcoma (PHL) is a very rare primary liver tumour. These tumours usually arise from intrahepatic vascular structures, gallbladder, or ligamentum teres. The pathogenesis of this disease is still unknown. We report a 53-year-old man with complaints of intermittent right upper abdominal pain for one month, decreased appetite, nausea, weight loss, and tea-coloured urination. The patient denied any complaints of defecation pattern. On physical examination, jaundice was present in both eyes and the whole-body skin, tenderness in the right hypochondriacal region, and enlarged liver with a lumpy surface. The laboratory examination demonstrated increased transaminase enzymes and bilirubin, while hepatitis B and C were negative. The patient underwent several tests for tumour markers, such as CA 19-9 50 (<37 U/mL), AFP 1.23 (<5.81 IU/mL), and CEA 0.83 (<3 ng/mL). Ultrasound demonstrated an enlarged liver, multiple liver nodules, and cholelithiasis. Meanwhile, the abdomen’s computerised tomography (CT) scan shows a solid heterogeneity image with an irregular border in segments 1 and 4b and a tumoral thrombus in the inferior vena cava. The diagnosis was confirmed by biopsy and immunohistochemistry (IHC); vimentin and smooth muscle actin (SMA) results were positive, while CD 34, CD 117, and cytokeratin were negative. Our patient was diagnosed with PHL stage IVa (T4N2M0). PHL is a particularly rare tumour with a poor prognosis. The patient died after one month of diagnosis. Diagnosis of PHL is challenging. It was based on clinical features, physical examinations, laboratory examinations, and other supporting investigations.